Milk Composition Traits of Hamdani Crossbreed Sheep Raised Under Extensive Management - Ali Osman TURGUT; Erman GÜLENDAĞ; Davut KOCA; Sefa ÜNER (ISPEC Journal of Agricultural Sciences)
This study aimed to reveal the milk composition traits of Hamdani crossbred sheep (Hcs) raised under extensive conditions. A total of 96 sheep milk samples were collected during the early lactation stage. Selected ewes did not have clinical mastitis or subclinical mastitis. Milk composition analyses were performed using milk autoanalyzer. Mean values for milk fat (%), solid non-fat (SNF) (%), protein (%), lactose (%), salt (%) and pH, conductivity (mS/cm), freezing point (⸰C) and density (kg/m3) in Hcs were determined as 7.49±0.15, 8.69±0.08, 4.13±0.04, 3.89±0.04, 0.62±0.01, 6.93±0.04, 4.05±0.07, -0.5±0.01, and 1.027.84±0.38 respectively. In correlation analysis, negative and significant correlations were detected between milk fat and protein (r=-0.368, p<0.001), milk fat and SNF (r=-0375, p<0.001) milk fat and lactose (r=-0.380, p<0.001). On the other hand, positive and significant correlations were detected between SNF and milk protein (r=0.999, p<0.001), SNF and salt (r=0.963, p<0.001), and SNF and lactose (r=0.976, p<0.001). As a result, the milk fat percentage of Hcs was higher compared to other native sheep breeds of Turkey. In addition, phenotypic variation for milk fat percentage was found to be high among individuals in the same flock. These findings may contribute to new studies to improve milk composition traits in Hamdani crossbred sheep.